2006
DOI: 10.1002/elps.200600203
|View full text |Cite
|
Sign up to set email alerts
|

Viability study of HL60 cells in contact with commonly used microchip materials

Abstract: This paper presents a study in which different commonly used microchip materials (silicon oxide, borosilicate glass, and PDMS) were analyzed for their effect on human promyelocytic leukemic (HL60) cells. Copper-coated silicon was analyzed for its toxicity and therefore served as a positive control. With quantitative PCR, the expression of the proliferation marker Cyclin D1 and the apoptosis marker tissue transglutaminase were measured. Flow cytometry was used to analyze the distribution through the different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…The investigations of adhesive properties of biological cells on chip have shown that there are no negative influences on the cellular conditions and behavior [347]. Other studies have shown that PDMS-based microfluidic systems can maintain normal cell viability for several weeks [348][349][350][351].…”
Section: Biocompatibility and Cell Viability Within Microfluidic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations of adhesive properties of biological cells on chip have shown that there are no negative influences on the cellular conditions and behavior [347]. Other studies have shown that PDMS-based microfluidic systems can maintain normal cell viability for several weeks [348][349][350][351].…”
Section: Biocompatibility and Cell Viability Within Microfluidic Systemsmentioning
confidence: 99%
“…Other studies have shown that PDMS-based microfluidic systems can maintain normal cell viability for several weeks [348][349][350][351]. The biocompatibility of microfluidic systems based on other materials such as silicon oxide, PDMS and glass were investigated, and all showed good cell viability [347].…”
Section: Biocompatibility and Cell Viability Within Microfluidic Systemsmentioning
confidence: 99%
“…Both reactions present some advantages and some limitations. The CuAAC, in contrast to the Staudinger ligation, requires the use of copper as a catalyst which can result in denaturation of the proteins [110] or can cause toxicity in living systems thus restricting its use in cells [111]. However, higher reaction rates have been described for the CuAAC or Huisgen reaction which makes this approach more suitable for studying dynamic systems or for animal studies where metabolic clearance of the probes should be minimized.…”
Section: Acyl-biotin Exchangementioning
confidence: 99%
“…1,2 The advantages of microfluidic devices for the study of cell apoptosis can circumvent the problems encountered by conventional methods and can greatly facilitate the study. [3][4][5][6][7] For example, Valero et al 4 demonstrated a microfluidic cell trap device to study apoptotic dynamics of HL-60 cells. Tamaki et al 7 developed a microsystem for cell experiments consisting of a scanning microscope detection system and a cell culture microchip to detect nonfluorescent biological substances with extremely high sensitivity without any labeling materials to monitor cytochrome c distribution during apoptosis in a single neuroblastoma-glioma hybrid cell in a glass microchip.…”
Section: Introductionmentioning
confidence: 99%
“…Tamaki et al 7 developed a microsystem for cell experiments consisting of a scanning microscope detection system and a cell culture microchip to detect nonfluorescent biological substances with extremely high sensitivity without any labeling materials to monitor cytochrome c distribution during apoptosis in a single neuroblastoma-glioma hybrid cell in a glass microchip. Wolbers et al 5,6 examined autofluorescence intensity to discriminate viable from apoptotic HL-60 cells on a microfluidic chip. Other microfluidic devices have been demonstrated for cell cytotoxicity screening, including cell traps in defined positions [8][9][10][11][12][13] ͑such as U-shape wires, polydimethylsiloxane ͑PDMS͒ wells, C-shaped rings with microsieves, holographic optical traps, and dielectrophoresis͒, microfluidic drug gradient generator, 9,[14][15][16] and patterned microsurfaces.…”
Section: Introductionmentioning
confidence: 99%